Control of Intrachain Morphology in the Formation of Polyfluorene Aggregates on the Single‐Molecule Level. Issue 10 (7th April 2020) - Wilhelm, Philipp; Blank, Dominik; Lupton, John M.; Vogelsang, Jan
Abstract: Controlling the morphology of π‐conjugated polymers for organic optoelectronic devices has long been a goal in the field of materials science. Since the morphology of a polymer chain is closely intertwined with its photophysical properties, it is desirable to be able to change the arrangement of the polymers at will. We investigate the π‐conjugated polymer poly(9, 9‐dioctylfluorene) (PFO), which can exist in three distinctly different structural phases: the α‐, β‐, and γ‐phase. Every phase has a different chain structure and a unique photoluminescence (PL) spectrum. Due to its unique properties and the pronounced spectral structure‐property relations, PFO can be used as a model system to study the morphology of π‐conjugated polymers. To avoid ensemble averaging, we examine the PL spectrum of single PFO chains embedded in a non‐fluorescent matrix. With single‐molecule spectroscopy the structural phase of every single chain can be determined, and changes can be monitored very easily. To manipulate the morphology, solvent vapor annealing (SVA) was applied, which leads to a diffusion of the polymer chains in the matrix. The β‐ and γ‐phases appear during the self‐assembly of single α‐phase PFO chains into mesoscopic aggregates. The extent of β‐ and γ‐phase formation is directed by the solvent‐swelling protocol used for aggregation. Aggregation unequivocally promotes formation of the more planar β‐ and γ‐phases. Once these lower‐energy more ordered structural phases are formed, SVA cannot return the polymer chain to the less ordered phase by aggregate swelling. Abstract : The π‐conjugated polymer poly(9, 9‐dioctylfluorene) (PFO) exists in three different phases: the α‐, β‐, and γ‐phase, which are associated with different chain morphologies. The β‐ and γ‐phases appear during the self‐assembly of single α‐phase PFO chains into mesoscopic aggregates. The extent of β‐ and γ‐phase formation is directed by the solvent‐swelling protocol used for aggregation.